Factors associated with Antenatal care among the Reproductive age of Women in Madhesh Province, Nepal - Devkota, Bijaya Mani (Kutumbha vani, 2024)
Antenatal care (ANC) is essential for maternal and neonatal health, where ANC acceptance varies significantly across different socioeconomic and demographic groups. This study aims to dissect the factors influencing ANC visits Madhesh Province, Nepal, using data from the 2022 Nepal Demographic and Health Survey (NDHS). The NDHS provides a rich dataset, the women of reproductive age who had at least one live birth in the preceding five years. The study focuses on a range of variables such as age, education, household wealth, and proximity to healthcare facilities, analyzing their impact on ANC visits, with the World Health Organization recommending a minimum of four visits for a healthy pregnancy. This study indicates that while age, religion, caste/ethnicity, and rural versus urban residency do not significantly impact ANC attendance, educational attainment shows a non-significant trend towards higher ANC visit rates among better-educated women. Interestingly, economic status does not generally affect ANC attendance except in the wealthiest group, which shows a near-significant increase in visit. Furthermore, significant negative relationship between birth order and ANC visits, suggesting that women with subsequent pregnancies are less likely to seek frequent antenatal care. The dynamics of ANC attendance targeted interventions aimed at improving maternal health services. By identifying the specific barriers and facilitators to ANC access, policymakers and healthcare providers can develop more effective strategies to boost ANC interest and improve pregnancy results. This study highlights the necessity of addressing both socio-economic differences and educational needs to ensure inclusive maternal health coverage.